Teachers need scientific and experiential knowledge on learning support: Recommendations for a teacher educator - Oswald, M.M. (South African Journal of Higher Education, 2019)
This paper discusses teachers’ lack of scientific (theoretical) knowledge on learning support in the classroom. This was one of the key findings of a basic exploratory qualitative study conducted in a South African secondary school. The study employed a Cultural-Historical Activity Theory (CHAT) framework. Six teachers from the school took part in the research. The results underscored their lack of scientific knowledge on learning support, confirming a perceived gap between theory and practice, contrary to CHAT’s take on the matter. The discussion highlights the value of scientific knowledge for the teacher and offers a number of recommendations for the work of the teacher educator.